Digital Sustainability: Leveraging Digital Technology to Combat Climate Change - Thabed Tholib Baladraf (The Journal of Indonesia Sustainable Development Planning, 2025)
Digital Sustainability: Leveraging Digital Technology to Combat Climate Change by Theo Lynn, Pierangelo Rosati, David Kreps, and Kieran Conboy is a collective work that positions itself at the crucial intersection between digital transformation and environmental sustainability. Published as part of the Palgrave Studies in Digital Business & Enabling Technologies series, this book reflects the growing academic and practical recognition that digital technologies play a dual role in contemporary society. On the one hand, they are frequently criticized for contributing to environmental degradation by escalating energy consumption, electronic waste, and the extraction of rare earth minerals. However, the same technologies also possess remarkable transformative potential to mitigate climate change, accelerate the achievement of sustainable development goals, and support the transition toward greener economic systems.